Die karakterisering van die Johannese Nikodemus: ’n narratologiese analise - Herman, LTI (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The characterization of the Johannine Nicodemus: a narratological analysis Exegetical commentary on Nicodemus is usually gained from historic-critical sources,but this type of information leaves many unresolved questions. For example: thequestion whether Nicodemus was a “true believer” or an “unbelieving seeker”remains a debatable topic. In this article a narratological approach is followed toexplain how the Johannine Nicodemus is characterised. It is argued that the implied author intentionally portrays Nicodemus as an ambiguous character in the narrative text.